Hydroalcoholic extract of Allium eriophyllum leaves attenuates cardiac impairment in rats with simultaneous type 2 diabetes and renal hypertension - Janahmadi, Z. (Res Pharm Sci, 2015)
Some species of Allium family have been shown to offer cardioprotection in animal studies. This study aimed at examining possible role of oxidative stress in the cardioprotective effects of hydroalcoholic extract of Allium eriophyllum in rats with simultaneous type 2 diabetes and renal hypertension. Six groups of male Spargue-Dawley rats (8-10 rats each) including a sham-control, a diabetic group, a renal hypertensive group, three groups of animals with simultaneous diabetes and hypertension receiving vehicle, or the extract at 30 or 100 mg/kg/day were used. Four weeks after receiving vehicle or extract, blood pressure, fasting blood glucose, and serum superoxide dismutase and glutathione reductase levels were measured, and isolated heart studies were performed. Systolic blood pressure, fasting blood glucose, coronary effluent creatine kinase-MB, infarct size and coronary resistance of diabetic hypertensive group receiving vehicle were significantly higher than those of the sham-control group and treatment with the extract prevented the increase of these variables. Moreover, rate of rise and decrease of left ventricular pressure, left ventricular developed pressure, rate pressure product and serum levels of superoxide dismutase and glutathione reductase of diabetic hypertensive group receiving vehicle were significantly lower than those the sham-control group, and treatment with the extract prevented the decrease of these variables. The findings indicate that hydroalcoholic extract of A. eriophyllum leaves, possibly by an antioxidant mechanism, protected against simultaneous diabetes and hypertension-induced cardiac dysfunction.